More stringent BITs, less ambiguous effects on FDI? Not a bit! - Axel Berger; Matthias Busse; Peter Nunnenkamp; Martin Roy (World Trade Organization (WTO), 2010)
We focus on investor-state dispute settlement provisions contained in various, though far from all, bilateral investment treaties as a possible determinant of BIT-related effects on bilateral FDI flows. Our estimation results prove to be sensitive to the specification of these provisions as well as the inclusion of transition countries in the sample. Stricter dispute settlement provisions do not necessarily result in higher FDI inflows so that the effectiveness of BITs as a credible commitment device remains elusive.
Keywords: F21; F23; K33; 330; Dispute Settlement; BITs; FDI flows; Investitionsgarantie; Internationale Schiedsgerichtsbarkeit; Direktinvestition; Kapitalimport; Schätzung; Welt